Lithic assemblages of Azokh Cave (Nagorno Karabagh, Lesser Caucasus): Raw materials, technology and regional context - Lena Asryan; Andreu Ollé; Norah Moloney; Tania King (Journal of Lithic Studies, 2014)
Azokh Cave is a Middle Pleistocene to Holocene site located in Nagorno Karabagh (Lesser Caucasus). The main entrance, Azokh 1, is a large cave that has two geological sequences (lower and upper) with nine geo-archaeological units of which only the upper ones (Units I to V) have a significant archaeological record.  The faunal remains and lithic artefacts in these units indicate aspects of human occupation, and exploitation of, and association with animals. The lithic artefacts presented here were recovered from Units V, III and II during the 2002 – 2009 excavation seasons. The available chronological data indicates an age between 293 – 100 Ka for these units. The operational chain is incomplete and artefacts found in the cave are primarily end-products dominated by flake-tools. The assemblage of Unit V is composed primarily of simple, unretouched flakes with a minimal presence of retouched flakes and cores. The Unit II lithic assemblage includes a substantial Levallois component, although with fewer cores and retouched flakes. There are very few flake tools in Unit III. While it is still difficult to assign the Unit V assemblage to a techno-typological group or complex (i.e. Acheulean, Mousterian or other local techno-complexes such as the Kudarian), the Unit II assemblage is clearly associated with Mode 3 or the Mousterian techno-complex. Different local and non-local raw materials were exploited in all units for the production of lithic artefacts, although the range of raw materials is more varied in Unit II. Local chert, flint and basalt were used most commonly, probably due to their easy accessibility. Limestone, jasper and sandstone, from local and non-local sources, are present in small quantities in Units V and II. Obsidian is the only raw material that possibly originates from more distant sources. Flint and chert appear to have been preferentially exploited for flake tool production in all units, but the toolmakers show a preference for better quality raw material (flint, basalt, obsidian) for retouched pieces in Units V and II, and for Levallois production in Unit II.